Assessing gender inequality in digital labour platforms in Europe - Paula Rodríguez-Modroño; Annarosa Pesole; Purificación López-Igual (Internet Policy Review)
In this article we analyse digital labour platforms from a feminist approach, revealing the pervasiveness of gender inequalities through segregation and the highly asymmetrical model of gender relations and social reproduction. Our findings after examining data from the COLLEEM survey on platform workers in 16 European countries show that women’s participation in platform work is concentrated in more ‘feminised’ tasks, their work intensity in the platform is lower, and they have slightly worse working conditions and earnings than men. Our results suggest the need for a new analytic approach to platforms, which emphasises labour force heterogeneity, worker dependence in platform work, and changing gender relations.